Project’s cost-benefit analysis for social infrastucture in tertiary education sector with sharia financing and the interest of waqifs: an Indonesia perspective - Surachman, Eko Nur; Mauliana, Afia; Yonimurwanto, Nugroho (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Purpose - This research was conducted to analyze how CWLS can be promising sources of infrastructure financing by presenting the benefit through the calculation of Cost-Benefit Analysis to the prospective waqifs.Method - This research used a mixed method: quantitative method using a Cost-Benefit Analysis (CBA) model by monetizing the costs and benefits of education infrastructure. CWLS is used as the source of financing to build it. Meanwhile, the qualitative method is conducted through focus group discussion to present and discuss the project benefit to the prospective waqifs.Result - The project delivered greater benefits in terms of positive NPV (IDR 937.437.495.257) and IRR (15,60%). The calculation attracts prospective waqifs that consider the non-monetary return in their investment, to invest in CWLS.Implication - The CWLS issuer should explain the greater benefits generated from the infrastructure financed by the CWLS to the prospective waqif. Cost-Benefit Analysis (CBA) is one of the tools to do it effectively.Originality - This study is one of a few studies exploring the CWLS instrument to finance public infrastructure, with its originality lying in the examination of the attractiveness of the CWLS to the prospective waqifs given the fact that the instrument offers zero profit in terms of financial return, but the beneficial reward from Allah SWT.